Beschreibung einer neuen Cossoninen-Art aus Persien (Coleoptera: Curculionidae). - Folwaczny, Bronislaw (Contributions to Entomology = Beiträge zur Entomologie, 1966)
A description is given of a new species Stereocorynes persieus n. sp. (Cossoninae) from Persia together with a determination key of the group in question. Nomenclatural Actspersicus Folwaczny, 1966 (Stereocorynes), spec. n.